Proteomics-based mortality prediction modeling in type 2 diabetes: new promise for personalized treatment and prevention - Gan, Lu; Wang, Changde; Liu, Xiaoying (BMC medicine, 2025)
The study highlighted the role of immune and inflammatory processes in mortality across both cohorts. [...]the identification of a T2D-specific mortality pathway related to insulin-like growth factor (IGF) transporter regulation suggests that unique biological processes within T2D patients may contribute significantly to early mortality risk. [...]despite the study’s robust double-validation approach, analyses of certain cause-specific deaths such as cancer-related mortality may suffer from insufficient statistical power due to limited sample sizes, follow-up duration, diabetes severity, and blood vessel damage assessments. [...]proteomics-based mortality prediction models represent a promising avenue for personalized treatment and prevention strategies.